2015
DOI: 10.1109/lwc.2014.2360179
|View full text |Cite
|
Sign up to set email alerts
|

Benefits of Improper Signaling for Underlay Cognitive Radio

Abstract: In this letter we study the potential benefits of improper signaling for a secondary user (SU) in underlay cognitive radio networks. We consider a basic yet illustrative scenario in which the primary user (PU) always transmit proper Gaussian signals and has a minimum rate constraint. After parameterizing the SU transmit signal in terms of its power and circularity coefficient (which measures the degree of impropriety), we prove that the SU improves its rate by transmitting improper signals only when the ratio … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
115
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 55 publications
(124 citation statements)
references
References 14 publications
6
115
1
Order By: Relevance
“…Similar DoF results were derived for the four-user interference channel in [14]. After that, a number of new works has emerged, and the payoffs of improper signaling have been revealed for different multiuser scenarios such as the interference channel [3][4][5]15], Z-interference channel [6,[16][17][18], broadcast channels with linear precoding [19,20], underlay and overlay cognitive radio networks [7,8,21] and relay channels [22,23]. More recently, in [24], the authors showed the advantages of improper signaling in a multiuser scenario where a point-to-point link coexists with a multiple access channel.…”
Section: Introductionsupporting
confidence: 55%
See 4 more Smart Citations
“…Similar DoF results were derived for the four-user interference channel in [14]. After that, a number of new works has emerged, and the payoffs of improper signaling have been revealed for different multiuser scenarios such as the interference channel [3][4][5]15], Z-interference channel [6,[16][17][18], broadcast channels with linear precoding [19,20], underlay and overlay cognitive radio networks [7,8,21] and relay channels [22,23]. More recently, in [24], the authors showed the advantages of improper signaling in a multiuser scenario where a point-to-point link coexists with a multiple access channel.…”
Section: Introductionsupporting
confidence: 55%
“…Since the PU is typically unaware of the SU, it is also assumed that the PU always transmits proper Gaussian signals, whereas the SU may transmit either proper or improper Gaussian signals depending on which signaling scheme performs better. This problem has been analyzed in [7], where it has been proven that the SU improves its rate by transmitting Gaussian improper signals if and only if (cf. Theorem 1 in [7]):…”
Section: A Motivating Examplementioning
confidence: 99%
See 3 more Smart Citations